Women’s view of the February Revolution: the opinion and role of women in historical events - Rudenko Victoria Evgenievna (Studia Humanitatis)
The article analyses how women recorded their thoughts and feelings in diaries, what themes and motives prevail in their records. The author examines the differences in the experiences and reactions of women from different cultures and peoples to political changes. Studying women’s diaries helps to take a fresh look at the revolution, to see it through the eyes of the participants who remain in the shadow of the big story. These sources allow us to assess the contribution of women to the all-Russian historical process, their influence on the course of events and the formation of public opinion. Special attention is paid to the differences in the perception of the revolution by women belonging to different cultures and ethnic groups living in the country. The study of women’s diaries allows us to expand our understanding of the revolution, to see it from a female perspective. The analysis of these personal testimonies makes it possible to assess the contribution of women and their influence on shaping public opinion. A comparative analysis allows us to identify common and special features in their reaction to the political changes of the state.